Molecular diagnosis of Turner's syndrome. - Gicquel, C (1992)
Turner's syndrome is a common disorder which occurs in around 1/3000 live births in girls. Diagnostic use of polymorphic DNA markers for the X chromosome could help to reduce the number of time consuming karyotype analyses needed. The M27 beta probe maps on the X chromosome to Xcen-Xp11-22 and in 83% of female subjects detects heterozygosity with multiallelic polymorphism. In Southern blotting, a single X chromosome yields a single hybridisation band. In this study, genomic DNA was extracted from leucocytes of 49 patients with Turner's syndrome (karyotypes: 45,XO, n = 29; 45,XO/46,XX, n = 4; 46,Xi(Xq), n = 1; 45,XO/46,Xi(Xq), n = 4; 45,XO/46,Xr(X), n = 4; 45,XO/46,XY, n = 4; 46,XXp-, n = 3), digested with EcoRI or HindIII, and analysed by Southern blotting. The molecular data for each patient were compared with DNA controls (homozygous 46,XX, heterozygous 46,XX and 46,XY DNA). A single band of reduced intensity compared to homozygous 46,XX control DNA was seen in 41 cases. Two hybridisation bands of different intensities were seen in four patients, in one of whom mosaicism was suspected on the basis of molecular analysis, despite a 45,XO karyotype. In four cases, Turner's syndrome failed to be detected: one 45,XO/46,XX mosaicism with only 4% of 45,XO cells and three distal Xp deletions. DNA analysis appears to be a useful and rapid tool in screening for Turner's syndrome and could be an alternative to cytogenetic analysis in diagnosing the disorder when severe growth retardation or delayed puberty are not accompanied by a Turner phenotype.